Nutritional and Oral Health Conditions in High School Students - Aguilera-Galaviz MSc, PhD, Luis Alejandro (2019)
To describe the relationship of oral diseases and nutritional status in high school students. A total of 203 high school students were evaluated nutritionally and orally according to the World Health Organization (WHO). A descriptive analysis, frequency, average tables, and a statistical analysis (Spearman correlation test) were performed with SPSS ver. 22 statistical software for Windows. Nutritionally, 146 students showed a normal Body Mass Index (BMI), six had malnutrition, 41 had overweight, and 10 had obesity. In the oral evaluation, the average number of caries was 3.08 ± 2.78, malnutrition showed 3.6, overweight 2.75, and obesity, 2.9. The risk of caries can be increases the greater the age, height, weight, skin-fold thickness, and periodontal disease. There is no significant statistical correlation between oral diseases and nutritional issues; however, qualitative analyses of patients with dental loss or oral diseases express significant deficiencies in their nutritional health.